2012
DOI: 10.1108/09590551211255956
|View full text |Cite
|
Sign up to set email alerts
|

The fruit and vegetable marketing chains in Thailand: policy impacts and implications

Abstract: PurposeThe main objective of this paper is to identify and study the marketing chains of fresh fruit and vegetables (FFV) in Thailand, the linkages of FFV farmers with supermarkets, and an evaluation of supermarket procurement systems. Another aim is to discuss the policies and implications relating to FFV and the connection of farmers with supermarkets in the context of Thailand.Design/methodology/approachThe paper uses both secondary and primary data. Public agencies' documents and published reports were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…The retailers, especially hypermarkets and supermarkets play an important role in fresh fruit market chain in Thailand. Srimanee and Routray (2012) revealed that fruit farmers have several marketing channels including wholesalers, cooperatives, specialist assembles, and exporters.…”
Section: Cooperatives In the Fruit Supply Chain In Thailandmentioning
confidence: 99%
See 1 more Smart Citation
“…The retailers, especially hypermarkets and supermarkets play an important role in fresh fruit market chain in Thailand. Srimanee and Routray (2012) revealed that fruit farmers have several marketing channels including wholesalers, cooperatives, specialist assembles, and exporters.…”
Section: Cooperatives In the Fruit Supply Chain In Thailandmentioning
confidence: 99%
“…However, supermarket procurement system regarding quality and quantity requirements makes it difficult for small-scale farmers to access the market. Various studies in developing countries have shown that farmers are confronted with many problems regarding the supply of products to supermarkets due to lack of knowledge and information, finance, and product supply uncertainty (Srimanee and Routray, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of hydroponic vegetables in "Kebunsayur Surabaya" prioritizes 'restaurants' as the consumers. farmers to markets through direct procurement while improving cultivation practice and participating in improving farmers' product quality (Srimanee and Routray, 2012). The number of large traders who are involved as intermediaries in the marketing process shows a long marketing channel.…”
Section: Resultsmentioning
confidence: 99%
“…Thailand has similar climatic condition as India and so is the food consumption pattern. The supply chain in fruits and vegetables however is much better developed in Thailand as compared to India (Srimanee and Routray, 2012). Supermarkets in Thailand account for 40 % of fruit and 30 % of vegetables in urban areas, but a lower percentage in the context of the entire country (Fig.…”
Section: Supply Chain Management Practices Followed In Other Countriesmentioning
confidence: 99%